Usulan Perbaikan Tata Letak Gudang dengan Metode Shared Storage untuk Mengurangi Jarak Tempuh Material handling - Anugrah Gusti Ramadhan; Amanda Sofiana (Jurnal TRINISTIK: Jurnal Teknik Industri, Bisnis Digital, dan Teknik Logistik, 2026)
Rapidly growing industries and advancing technologies bring new complexities to the manufacturing industry, including non-optimal warehouse layouts. PT. XYZ, a building material provider, faced challenges in its warehouse management and material handling processes. These challenges include disorganized product arrangement and improper product placement, resulting in low outbound efficiency. A good finished product warehouse layout can help the company avoid losses, reducing material handling costs by minimizing travel distance, and simplify warehouse utilities. The shared storage method is proposed to solve this problem, with the placement of goods based on the FIFO (First In First Out) principle, so that goods that are frequently in and out are placed near the exit. Based on previous research, the shared storage method has proven effective in improving space efficiency and reducing material handling distance. This study aims to propose a more effective placement of goods and maximize warehouse capacity. The results show that the total material handling distance can be reduced from 79,997.25 meters to 42,029 meters, with an increase in capacity from 2400 pallets to 2648 pallets.